New records of two carangid species from the south-east coast of Sicily (Ionian Sea) and considerations about their presence and abundance - Tiralongo, Francesco (Array, 2018)
New records of Pseudocaranx dentex (Bloch & Schneider, 1801) and Seriola fasciata (Bloch, 1793) are reported from the Mediterranean Sea. During the period 2013-2017, we have collected several records of both species from the south-east coast of Sicily (Ionian Sea). On the basis of our and published data, we can consider S. fasciata as a relatively common species in the area, commonly caught with purse seine around FADs in summer and autumn; while, P. dentex remains basically a rare species, occasionally caught with trammel nets or gillnets. This work represents the first well-documented records of both carangid species in the south-east coast of Sicily.